An application framework to systematically develop complex learning resources based on collaborative knowledge engineering - Ganán, David; Caballé, Santi; Conesa, Jordi; Conesa, Fatos (Zielona Góra: Uniwersytet Zielonogórski)
This contribution proposes software infrastructure to support new types of learning methodologies and resources based on collaborative knowledge engineering by means of an innovative application framework called the virtualized collaborative sessions framework (VCSF). The VCSF helps meet challenging collaborative knowledge engineering requirements in online learning, such as increasing group members` learning performance during the on-line collaborative learning process.
Keywords: software infrastructure; application framework; collaborative knowledge engineering; on-line collaborative learning; discussion forums; virtualization; collaborative sessions; collaborative complex learning resources